Discovering the Changes in Gendering of Products: Case of Woman in ‘Bikerni Community’ in India - Jain, Varsha; Bharadwaj, Kriti; Bansal, Amrita; Natarajan, Vivek S (Border Crossing, 2016)
In the Indian society, gender roles have played an important role in shaping the culture. However, due to technological advancements and change in societal needs, there is an evolution in the gender roles. This evolution has created a need to understand the gendered products from a new perspective. Therefore, this paper tries to discover the factors of consumption of gendered products and role of social media in shaping the consumption pattern and motivation of women in biking industry in India. Subsequently, to address the objectives, qualitative methods such as in-depth interviews, netnography and projective techniques are applied and data is analyzed further. With the help of data analysis, it has been found that that Indian woman is motivated by a quest for freedom, independence and empowerment. The families and close-knit communities that they are part of, such as Bikerni Association of India, help them participate in a hyper-masculine product market.